Effects of Ag on morphology and catalytic performance of iron catalysts for Fischer–Tropsch synthesis1. Issue 72 (6th August 2015) - Zhang, Yulan; Ding, Mingyue; Ma, Longlong; Wang, Tiejun; Li, Xinjun
<x xml:space="preserve">Abstract</x> Ag-doped porous composites were synthesized and employed as catalysts. Active Fe3O4 was interspersed on the surface of the Ag promoter, which was used to enhance the catalytic activity and the desired hydrocarbon yield.